Expert consensus on adjustment of pre-donation blood pressure screening requirements for blood donor population in China - Expert Panel on Blood Pressure Screening Strategies for Blood Donor Selection (Zhongguo shuxue zazhi)
Standards for blood donors selection are established to ensure the safety of both donors and recipients, as well as the quality of blood products and an adequate blood supply. Medical conditions are typically treated as critical indicators in these standards. In practice, however, blood donor eligibility criteria are often based on local regulatory requirements or practical experience rather than evidence-based medical research. National standards in China specify regulations regarding hypertension and pre-donation blood pressure screening. Nevertheless, variations in the measurement environment may compromise the standardization and accuracy of blood pressure readings. Additionally, the common phenomenon of "white-coat hypertension" further complicates blood pressure assessment. Excluding donors solely due to blood pressure exceeding predefined thresholds risks unnecessary deferrals and donor attrition. This expert consensus evaluates the current prevalence and management of hypertension in China, analyzes the safety implications of blood pressure levels in blood donation, and synthesizes practices from diverse countries and regions. It provides evidence-based recommendations for refining pre-donation blood pressure measurement protocols and eligibility assessments, aiming to offer guidance for the optimization of blood pressure screening strategies for Chinese blood donor population.